2022
DOI: 10.3390/ijerph191710956
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Our Relationship: Dyadic Interactions Supported by Technology for People with Dementia and Their Informal Caregivers

Abstract: Impaired memory function and challenges in communication affect the ability of people living with dementia to interact with family caregivers socially. The onset of dementia in a family member and the communication challenges that follow can lead to conflict, isolation and loss of closeness in the relationship. I-CARE is a tablet-based technology providing leisure activities specifically designed for people living with dementia to do in tandem with caregivers. The intention is that caregiving dyads engage with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
0
10
0
2
Order By: Relevance
“…The topic of engagement and social interaction was highlighted in 64 studies. They differentiated between cases where DATs increased social interaction [20], [28], [29], [34], [35], [38], [41], [45], [54], [59], [64], [70], [72], [80], [82], [83], [85], [100], [102], [112], [113], [123], [129], [131], [133], [134] and fostered higher engagement (i.e., in therapy settings) [23], [26], [29], [34], [36]–[38], [40]–[42], [45], [53]–[55], [57], [60], [62], [63], [66]–[68], [70], [73], [76]–[79], [84], [85], [87], [88], [90], [91], [96], [100], [109], [112], [114], [116], [118], [122], [127], [130], [131], [133], [135], [136], [138], [139], [141].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of engagement and social interaction was highlighted in 64 studies. They differentiated between cases where DATs increased social interaction [20], [28], [29], [34], [35], [38], [41], [45], [54], [59], [64], [70], [72], [80], [82], [83], [85], [100], [102], [112], [113], [123], [129], [131], [133], [134] and fostered higher engagement (i.e., in therapy settings) [23], [26], [29], [34], [36]–[38], [40]–[42], [45], [53]–[55], [57], [60], [62], [63], [66]–[68], [70], [73], [76]–[79], [84], [85], [87], [88], [90], [91], [96], [100], [109], [112], [114], [116], [118], [122], [127], [130], [131], [133], [135], [136], [138], [139], [141].…”
Section: Resultsmentioning
confidence: 99%
“…62 of the included studies demonstrated that digital therapeutics play a significant role in promoting social interaction and engagement [20], [23], [26], [28], [29], [34]–[38], [40]–[42], [45], [53]–[55], [57], [59], [60], [62]–[64], [66]–[68], [70], [72], [73], [76]–[80], [82], [84], [85], [87], [88], [90], [91], [96], [100], [102], [109], [112]–[114], [116], [118], [123], [127], [129]–[131], [133]–[136], [138], [139], [141], including other DATs from the patient monitoring [123] and care support categories [53], [95].…”
Section: Resultsmentioning
confidence: 99%
“…The three core elements of enrichment have been operationalized following the definition proposed by Cartwright et al (29), outlined in detail under "Concept" and summarized in Table 1. The process of operationalizing and contextualizing the core elements of enrichment was supported by findings from our preceding empirical studies focusing on dyadic relationships in dementia caregiving (48,49), as well as the work of the INTERDEM Social Health Taskforce (30)(31)(32)(33)(34) (Supplementary Appendix 1). Within this context, this review mapped out existing types of psychosocial interventions and components that contribute to enrichment in dyadic relationships in formal and informal dementia caregiving contexts.…”
Section: Objectivesmentioning
confidence: 86%
“…The first core element, acquired symbolic meaning , refers to the significance, value or intent of an activity or an object, with symbolic meaning extending beyond the utility of the given object or activity ( 29 ). Supported by empirical findings ( 49 ), this core element of enrichment is operationalized as shared activities that can lay the groundwork for positive relationship gains. A key element of psychosocial interventions is that they serve as a communication channel for PLWD to engage, interact and talk with others ( 31 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…This has been challenged by activists and scholars within and outside the AT community [17]. There is increasing recognition of the importance of social and cultural factors in AT use and growing evidence that social relationships can enable PwADRD to lead meaningful lives and improve the well-being of their caregivers [17,18]. Therefore, "independence" is no longer suffice as the primary goal of AT design.…”
Section: Independence and Interdependence In Active Assistive Livingmentioning
confidence: 99%